Lactobacillus: Friend or Foe for Systemic Lupus Erythematosus? - Wang, Weijie; Fan, Yongsheng; Wang, Xinchang (Frontiers in Immunology, 2022)
The cause of Systemic Lupus Erythematosus (SLE) remains largely unknown, despite the fact that it is well understood that a complex interaction between genes and environment is required for disease development. Microbiota serve as activators and are essential to immune homeostasis. Lactobacillus is thought to be an environmental agent affecting the development of SLE. However, beneficial therapeutic and anti-inflammatory effects of Lactobacillus on SLE were also explored. The discovery of Lactobacillus involvement in SLE will shed light on how SLE develops, as well as finding microbiota-targeted biomarkers and novel therapies. In this review, we attempt to describe the two sides of Lactobacillus in the occurrence, development, treatment and prognosis of SLE. We also discuss the effect of different strains Lactobacillus on immune cells, murine lupus, and patients. Finally, we try to illustrate the potential immunological mechanisms of Lactobacillus on SLE and provide evidence for further microbiota-targeted therapies.